The influence of brand image, Brand Personality and Brand Experience on Brand Love and Their Impact on Brand Loyalty of Cellular Card Users - gusti noorlitaria achmad, gusti noorlitaria achmad; syarifah Hudayah, syarifah Hudayah; Saida Zainurossalamia ZA, Saida Zainurossalamia ZA; shibghati Mutia Hasanah, shibghati Mutia Hasanah (AFEBI Economic and Finance Review, 2020)
Abstract The purpose of this research is to know: (1) influence of brand image to brand love (2) influence of brand personality to brand love, (3) influence of brand experience to brand love (4) influence of brand image to brand loyalty (5) influence of brandexperience to brand loyalty, (6) the influence of brand love on brand loyalty. This research was conducted using a sample of 131 people and data are taken by giving respondents structural questionaires. In terms of data analysis, this research used Partial Least Square (PLS)